Application of Floyd Algorithm to find the Shortest Path for Marketing the Gum Arabic in Sudan - Abualez Alamin Ahmed Ali; Musa Adam Abdulla; Nagia Mohammed Daffala Mohammed; Yasmeen Sirag Osman Mohammed (African Journal of Advanced Pure and Applied Sciences, 2023)
This paper explores the application of Floyd’s algorithm to optimize the marketing strategy for Gum Arabic in Sudan. Recognizing the unique challenges associated with Gum Arabic marketing, we leverage the algorithm’s ability to identify the shortest paths and streamline transportation logistics. Using MATLAB as the implementation tool, we analyze the initial matrices, apply the algorithm iteratively, and uncover optimized routes that minimize distances. The results demonstrate significant improvements in market accessibility and transportation efficiency. Through visual representations, the study provides tangible evidence of Floyd’s algorithm’s effectiveness in real-world marketing contexts. The findings not only contribute to the enhancement of Gum Arabic distribution but also underscore the broader potential of algorithmic approaches in optimizing commodity marketing networks. This study not only addresses immediate marketing concerns but also encourages further exploration of algorithmic strategies in similar supply chain optimization scenarios. After completing the algorithm, we found that the route with smallest distance is (Nyala, Alaobied, Omdurman, Atbara, Bort Sudan) with length 1650 Km.